PKMS Karang Taruna in Creating a Creative Economy through Training of Sport Therapist and Fitness Trainer in Mandalika Area - khaerul Anam; Lilik Evitamala; Dedi Rizwandi (Asian Journal of Community Services, 2022)
Kuta Mandalika is a special economic area that will become a tourist destination to visit and exercise, especially since the international standard MotoGP has been built. The purpose of this community service is to increase skills and new economic opportunities so that the economy of Karang Taruna Pujut District can continue to grow and develop. the effort that must be made is to develop sub-skills in fitness services and sports therapists located in the Mandalika Special Economic area. Outcomes to be achieved through the Indonesia Tangguh UKM program with the slogan "recover together, recover stronger" include 1. an increased understanding of being a sports therapist 2. increased understanding of being a personal trainer 3. Increased number of customers, 4. Improved management of SMEs through financial systems, and marketing promotions. The results of the activity evaluation show that almost 70% of the material is absorbed, while 90% of practice. This result is due to the use of scientific language, but it has a positive impact on improving skills in the field and continuing to practice